Theoretical studies of liquids by computer simulations: the water-acetone mixture. - Freitas, LCG; Cordeiro, JMM; Garbujo, FLL (Elsevier B.V., 1999)
Monte Carlo simulation results for pure liquid acetone and water-acetone mixtures calculated in the isothermal and isobaric (NPT) ensemble at T=298K and p=1.0atm are presented. The TIP4P model was used for water and optimized potential for liquid simulation (OPLS) force field parameters used for acetone. The results obtained for the average configurational energy as a function of the mole fraction are in good accord with experimental data. Energy partitioning and co-ordination numbers results calculated for equimolar water-acetone solution are compared to similar data obtained for other water-organic liquid mixtures. These results show an increase in water-water interaction energy and co-ordination numbers when the interaction between water and organic liquid molecules decrease. Distribution functions for pure liquid acetone and water-acetone mixtures are presented. Dipole-dipole angular correlation functions obtained for pure liquid acetone show a predominance of dimers with parallel alignment of dipole moments. Radial distribution functions from water-acetone interaction show characteristic features of hydrogen bonded liquids. Radial and angular distribution functions for water-water correlation calculated in pure water and in equimolar water-acetone mixture are compared, showing very similar features in both systems. (C) 1999 Elsevier B.V. B.V. All rights reserved.